Thrombotic Events in COVID-19 Are Associated With a Lower Use of Prophylactic Anticoagulation Before Hospitalization and Followed by Decreases in Platelet Reactivity - Clark, Chantal C.; Jukema, Bernard N.; Barendrecht, Arjan D.; Spanjaard, Judith S.; Jorritsma, Nikita K. N.; Smits, Simone; de Maat, Steven; Seinen, Cor W.; Verhoef, Sandra; Parr, Naomi M. J.; Sebastian, Silvie A. E.; Koekman, Arnold C.; et al. (Frontiers in Medicine, 2021)
Background: Coronavirus disease of 2019 (COVID-19) is associated with a prothrombotic state and a high incidence of thrombotic event(s) (TE). Objectives: To study platelet reactivity in hospitalized COVID-19 patients and determine a possible association with the clinical outcomes thrombosis and all-cause mortality. Methods: 79 hospitalized COVID-19 patients were enrolled in this retrospective cohort study and provided blood samples in which platelet reactivity in response to stimulation with ADP and TRAP-6 was determined using flow cytometry. Clinical outcomes included thrombotic events, and all-cause mortality. Results: The incidence of TE in this study was 28% and all-cause mortality 16%. Patients that developed a TE were younger than patients that did not develop a TE (median age of 55 versus 70 years; adjusted odds ratio (AOR) = 0.96 per 1 year of age, 95% confidence interval (CI) 0.92-1.00; p = 0.041). Furthermore, patients using preexisting thromboprophylaxis were less likely to develop a thrombotic complication than patients that were not (18% versus 54%; AOR = 0.19, 95% CI 0.04-0.84; p = 0.029). Conversely, having asthma strongly increased the risk on TE development (AOR = 6.2, 95% CI 1.15-33.7; p = 0.034). No significant differences in baseline P-selectin expression or platelet reactivity were observed between the COVID-19 positive patients (n=79) and COVID-19 negative hospitalized control patients (n=21), nor between COVID-19 positive survivors or non-survivors. However, patients showed decreased platelet reactivity in response TRAP-6 following TE development. Conclusion: We observed an association between the use of preexisting thromboprophylaxis and a decreased risk of TE during COVID-19. This suggests that these therapies are beneficial for coping with COVID-19 associated hypercoagulability. This highlights the importance of patient therapy adherence. We observed lowered platelet reactivity after the development of TE, which might be attributed to platelet desensitization during thromboinflammation.